Legal Analysis Of The Implementation Of Execution Parate Monitoring Rights By Pt. Bank Of Papua - Muhammad Husni Ingratubun (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2022)
The aim of this research is to determine the implementation of parate execution carried out by PT. Bank Papua and to find out form of execution of collateral objects charged with Rights Dependents.The method used in this research is approach normative law and empirical legal approaches. Legal research Normative is legal research that places law as a norm, rule and statutory regulation. Whereas Empirical legal research is legal research that will provide a complete understanding and response to the law in the context of norms to answer questions about the implementation of the rights execution parate dependents. The research results show that the implementation of the execution parate carried out by PT. Bank Papua is not running well because there is resistance from the debtor who does not want the object the collateral is auctioned off. Pursuant to Article 6 of the Bill of Rights Dependents then the creditor has the right to carry out parate execution without requires a fiat of execution from the Court